The Role of Teachers in Improving Student Discipline - Muslimah Sahyuni; Muhammad Zalnur; Surya Anisah Nasution; Siti Zubaidah; Rita Melianda (Suluah Pasaman, 2025)
The lack of discipline among students in the girls' dormitory of the Islamic boarding school was evident from the results of the researcher's observations. The Islamic boarding school enforced discipline through the role of teachers in the dormitory. This study aims to examine the extent of discipline in carrying out activities in the dormitory. This study uses a qualitative method with a descriptive qualitative approach. The data sources were fifteen informants consisting of three dormitory supervisors, eight teachers per room area, and four students living in the dormitory. The results of this study show that there are three forms of discipline in the girls' boarding school of the Islamic boarding school, namely: i) the form of student discipline in dormitory activities, ii) the role of teachers in improving student discipline in the girls' dormitory, iii) factors that hinder student discipline in the girls' dormitory. All of these findings are expected to serve as guidelines for dormitory administrators/teachers, particularly in improving student discipline, and as reference material for future researchers studying the same context and different issues.